KESINTASAN BEBERAPA JAMUR ANTAGONIS PADA BUAH CABAI DAN POTENSINYA DALAM MENEKAN PENYAKIT ANTRAKNOSA YANG DISEBABKAN OLEH COLLETOTRICHUM GLOEOSPORIOIDES - ., Nurbailis; ., Martinius; Naipinta, Rizka (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Persistence of several antagonistic fungus on chilli and its potential to suppress anthracnose disease caused by Colletotrichum gloeosporioides. Anthracnose disease caused by C. gloeosporioides is one of the important diseases on chilli because its directly gives negative impact on chilli production. The aim of this research was to obtain the superior antagonistic fungi that have ability to persist on chili fruit and potential to control anthracnose disease caused by C. gloeosporioides  The experiment consist of two units: 1. Testing of persistence ability of antagonistic fungi on chilli fruit, 2. Testing the potential of antagonistic fungi to suppress anthracnose disease on chilli fruit. Both of the test used Randomized Block Design (RBD) with 10 treatments and 4 replication, each of replication consist of 4 chilies fruit. Those treatments were Trichoderma-PP1, Trichoderma-PP3, Trichoderma-AG2, Trichoderma-PYK3, Paecilomyces-PP6, Paecilomyces-PP7, Paecilomyces-AG4, Paecilomyces-PYK4, Aspergillus PP2 and without antagonistic fungi (control). The result indicated that all antagonistic fungi isolate could persist on chili fruit. The highest persistence were Trichoderma-PP3 and TrichodermaAG2 (95.83%) and the lowest belonged to Paecilomyces-PP7 (50%). Trichoderma-PP3 and Trichoderma-AG2 were the best isolates for suppressing anthracnose disease caused by C. gloeosporioides.